View-Dependent Tessellation and Simulation of Ocean Surfaces - Anna Puig-Centelles; Francisco Ramos; Oscar Ripolles; Miguel Chover; Mateu Sbert (The Scientific World Journal)
Modeling and rendering realistic ocean scenes have been thoroughly investigated for many years. Its appearance has been studied and it is possible to find very detailed simulations where a high degree of realism is achieved. Nevertheless, among the solutions to ocean rendering, real-time management of the huge heightmaps that are necessary for rendering an ocean scene is still not solved. We propose a new technique for simulating the ocean surface on GPU. This technique is capable of offering view-dependent approximations of the mesh while maintaining coherence among the extracted approximations. This feature is very important as most solutions previously presented must retessellate from the initial mesh. Our solution is able to use the latest extracted approximation when refining or coarsening the mesh.